LEARNING STRATEGY IN WRITE BEGINNING IN CHILDREN WITH DISLEXIA - Arif Mustofa; Suyadi Suyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2021)
This research is a qualitative study of Whole Word case studies and VAKT (Visual, Auditory, Kinesthetic, and, Tactile) strategies for children with special needs to develop functional skills in reading and writing beginning. The subjects in this study were selected using the procedure for determining the subject in qualitative research proposed by Sarantakos in Poerwandari (2005), namely: 1) Directed not at a large number of participants but at typical cases according to the specificity of the research problem, 2) Directed at context fits and is not used for representativeness in the sense of random numbers or events. From the explanation above, the researcher then determined the research subjects/participants as follows: 1) The subject was a child aged 8 years who was at the elementary level of elementary education, and 2) the subject was a child with special needs who experienced obstacles in developing writing and reading skills. Data collection methods were carried out through observation, interviews, and documentation of field notes during data mining. Data analysis was performed by comparing the subject's initial condition before being stimulated with the subject's initial condition after stimulation was carried out. The results of data analysis indicate that the application of the whole word approach and the VAKT strategy can be used to help develop reading and writing skills for children with special needs.